(untitled) (Papeles, 2022)
The development of emotional intelligence has become a necessity; therefore, it is essential that a part of it be dedicated in the school curriculum throughout all stages of education, from early childhood education to adulthood. An intervention proposal is made through the use of a new didactic methodology called Learning Styles Corners in Primary, Secondary and Higher Studies (REAPSES) to work on interpersonal relationships and the cohesion of the class group. Activities are proposed to be carried out in each corner of learning style (active, pragmatic, reflective and theoretical) through a concrete emotion, in this case empathy. This proposal is based on the need for a school in the face of the inappropriate behavior of some students in 4th grade, for which the use of the Emotional Intelligence inventory of BarOn, the learning styles questionnaire and the sociogram as tools for initial and final evaluation. It is thought that the implementation of the same will be able to achieve an improvement of the coexistence in the class group, allowing the knowledge of the students themselves and their way of acquiring the information.